2003
DOI: 10.1074/jbc.m206999200
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones Block Fatty Acid Release by Inducing Glyceroneogenesis in Fat Cells

Abstract: Thiazolidinediones are used to treat type 2 diabetes mellitus because they decrease plasma glucose, insulin, triglyceride, and fatty acid levels. Thiazolidinediones are agonists for peroxisome proliferator-activated receptor ␥, a nuclear receptor that is highly expressed in fat tissue. We identify glyceroneogenesis as a target of thiazolidinediones in cultured adipocytes and fat tissues of Wistar rats. The activation of glyceroneogenesis by thiazolidinediones occurs mainly in visceral fat, the same fat depot t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
141
2
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 28 publications
14
141
2
5
Order By: Relevance
“…The glycerol-3-phosphate that is required for triglyceride synthesis during re-esterification of FFA can be produced in adipose tissue through two pathways: (a) in the presence of glucose in media or in the postprandial state, glycolysis is a classical source of glycerol-3-phosphate whereas (b) in the absence of glucose in the media or during fasting when glycolysis is suppressed, the glycerol-3-phosphate can be produced by the glyceroneogenesis, 12,13 where phosphoenolpyruvate carboxykinase (PEPCK) is considered to be a key enzyme in the regulation of glyceroneogenesis and subsequent FFA re-esterification. 14,15 In the current study, we found that expression of transgenic resistin in adipocytes induced significant reduction of FFA re-esterification. In addition, the expression of the Pck1 gene encoding the PEPCK enzyme was significantly reduced in epididymal fat tissue of the SHR-Resistin transgenic strain compared to SHR controls.…”
Section: Discussionsupporting
confidence: 56%
“…The glycerol-3-phosphate that is required for triglyceride synthesis during re-esterification of FFA can be produced in adipose tissue through two pathways: (a) in the presence of glucose in media or in the postprandial state, glycolysis is a classical source of glycerol-3-phosphate whereas (b) in the absence of glucose in the media or during fasting when glycolysis is suppressed, the glycerol-3-phosphate can be produced by the glyceroneogenesis, 12,13 where phosphoenolpyruvate carboxykinase (PEPCK) is considered to be a key enzyme in the regulation of glyceroneogenesis and subsequent FFA re-esterification. 14,15 In the current study, we found that expression of transgenic resistin in adipocytes induced significant reduction of FFA re-esterification. In addition, the expression of the Pck1 gene encoding the PEPCK enzyme was significantly reduced in epididymal fat tissue of the SHR-Resistin transgenic strain compared to SHR controls.…”
Section: Discussionsupporting
confidence: 56%
“…Two studies found a reduction in the release of lipolytic products from rodent WAT explants and 3T3-L1 adipocytes [5,6]. These were, however, primarily designed to examine NEFA re-esterification under conditions that may have favoured the latter process.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its effect on plasma NEFAs, PPARγ agonism might also be expected to reduce lipolysis; however, previous studies investigating this issue have produced conflicting results. Whereas some studies have reported lower in vitro rates of glycerol and NEFA release from WAT [5,6], others that include in vivo NEFA kinetic approaches [4,7] suggest that PPARγ agonism stimulates lipolysis, an effect that would be counteracted by its concomitant action on NEFA reuptake and re-esterification.…”
Section: Introductionmentioning
confidence: 98%
“…Thiazolidinediones induce G3P synthesis through glyceroneogenesis and glycerol phosphorylation [33]. We showed that glyceroneogenesis was the main contributor pathway for fatty acid reesterification in rat adipose tissue in both basal and thiazolidinedione-stimulated conditions [19]. This result was reinforced by elegant in vivo experiments from Chen et al [34], in which mass isotopomer analyses in mice confirmed the major contribution of glyceroneogenesis to thiazolidinedione-induced triacylglycerol synthesis, with a very minor role of glycerol phosphorylation.…”
Section: Discussionmentioning
confidence: 82%
“…This pathway occurs also in liver, in addition to gluconeogenesis [18]. Recent data identified glyceroneogenesis as a thiazolidinedione target in cultured rat adipocytes and adipose tissue, which was the result of induction of its key enzyme, the cytosolic isoform of phosphoenolpyruvate carboxykinase (PEPCK-C) [19]. In cultured explants from human s.c. adipose tissue, the prototype thiazolidinedione rosiglitazone increased the expression of the gene endoing PEPCK-C (PCK1) and glyceroneogenesis [20,21].…”
Section: Introductionmentioning
confidence: 99%